FORMULATION OPTIMIZATION AND IN VIVO EVALUATION OF ORODISPERSIBLE TABLETS OF ALMOTRIPTAN FOR THE EFFECTIVE TREATMENT OF MIGRAINE - SIRISHA Y (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: The present research work focuses on formulation, optimization, and in vivo evaluation of the orodispersible tablets of almotriptan to achieve the desired bioavailability and give a rapid relief from the migraine headache. Methods: The optimization was done using 32 factorial design considering the three superdisintegrants as factors and minimum (0) and maximum 2 levels using response surface methodology, and the formulation was subjected to several in vitro evaluation studies. Along with stability studies for 6 months, the optimized stable formulation of almotriptan was subjected to in vivo studies employing animal models (rabbits) to determine the plasma concentration of the drug within the required time after oral administration, and the pharmacokinetic parameters such as Cmax, Tmax, area under the curve (AUC), and others were calculated. In vitro–in vivo correlation was done by deconvolution using Wagner–Nelson method, and the graphs were plotted to report the correlation of drugs. Results: The almotriptan formulation F16 containing mannitol as diluent and cross-povidone 8 mg as superdisintegrant has shown better release of drug, i.e., 98.87% in 30 min, all the pre- and post-compression parameters were within limits. The optimized formulation has shown 98.27% drug release in 15 min, and the same formulation was taken for an in vivo study, which gave greater Cmax, Tmax, and AUC values compared to the marketed formulation. The in vitro–on vivo correlation was well established with an R2 value of 0.9908. Conclusion: Almotriptan orodispersible tablets have been successfully formulated and evaluated, and show rapid release with enhanced bioavailability.